Menilai Kembali Kebijakan Hukum Perlindungan Lingkungan Hidup Dalam Undang-Undang Cipta Kerja Untuk Mendukung Kelestarian Ekologi - Isti Puspitasari; Erviyanti Rosmaida; Christloy Totota Karo Karo; Irwan Triadi (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
The purpose of this article is to find out how to change environmental legal policy into environmental law into the Job Creation Law and to find out the appropriate efforts to address changes in environmental legal policy from the environmental protection perspective of the Job Creation Law. The research method presented in this article uses a normative legal approach, namely descriptive analysis. The results of the study in the article show that the concept of environmental law has become a legal policy that activates various instruments that regulate environmental problems in Indonesia, both regulatory and planning instruments. Finally, the aim of environmental legal policy is to ensure the implementation of sustainability in Indonesia from an environmental perspective. Efforts that must be made to address changes in environmental legal policy from the environmental protection perspective of the Job Creation Law are: 1) Simplification of permits; 2) Strict responsibility and 3);Restrictions on environmental rights. These three things cannot be taken lightly, so as not to have the worst impact on the quality of the environment. The Job Creation Law and its derivatives already existed until legal action was taken to revoke them. This is an important consideration where the Government must continue to develop good faith partnerships with the community to implement the Work and its consequential provisions.